Cadmium concentrations in German soybeans are elevated in conurbations and in regions dominated by mining and the metal industry. (5th February 2019) - Franzaring, Jürgen; Fangmeier, Andreas; Schlosser, Sonja; Hahn, Volker
Abstract: BACKGROUND: Cadmium (Cd) is a mobile heavy metal and soybeans accumulate more of this element compared to other grain crops. Because vegan and vegetarian lifestyles are increasingly popular, plant‐based diets should be free from contaminants. Cd minimization has recently been identified as a breeding aim in addition to protein and oil levels. It is also important to consider the regional variability of Cd in crops. RESULTS: A large sample collection ( n = 602) was subjected to Cd analyses. Soybeans were grown using a standard protocol by private gardeners in a citizen science program. Some 12.5% of samples exceeded European Union limits, although Cd concentrations and exceedances showed regional variation around the national mean (0.13 mg kg −1 ). Contamination was higher in densely populated regions, possibly as a result of the long‐term emissions of heavy metal loaded dusts from industry, traffic and energy production. Cd concentrations were also elevated in regions once characterized by mining and heavy industry. Values were low overall in rural areas and agricultural regions despite potential inputs via phosphate fertilizers. CONCLUSION: Grain Cd levels are highly variable across Germany. Soybean farming may be problematic in regions with a long history of mining and heavy metal deposition. © 2018 Society of Chemical Industry